Indirect cooling of the cutting tool with a pumped two-phase system in turning of AISI 1045 steel - Ingraci Neto, Rubens R. [UNESP] (2016)
The elimination of cutting fluids’ usage is one of the great challenges of sustainable manufacturing. Various devices and alternative techniques have been developed, but their results are limited, as well as their commercial applications. Most of them require drastic changes in the cutting tools or machine tools, or operate with nonevaporative cooling cycles, with low cooling capacity. The aim of this study is to present a device that overcomes these limitations and stands as an alternative to the application of cutting fluid without sacrificing the performance of the machining. Thus, a toolholder is developed that enables the indirect cooling of the cutting tool with a pumped two-phase system using the coolant R141b (vaporization temperature of 32 °C). In this system, the geometry of the cutting tool is not changed and there is no direct contact with the refrigerant, so there is no contamination or piece cleaning necessity. Moreover, the system operates in a closed circuit with only 5 l of coolant that does not require constant treatment. The performance of the proposed method of internal cooling is evaluated by turning tests of AISI 1045 steel under conditions of continuous and interrupted cut. The turning tests compare the lives of the uncoated cemented carbide cutting tools, their temperatures, and wear mechanisms acting during machining with the internal cooling method, or cutting fluid or dry cutting. The results show that the internal cooling is able to extend the life of cutting tools by 58 % in interrupted cutting and by 7 % in continuous cutting in relation to the cutting fluid application and by 13 and by 45 % in relation to the interrupted and continuous dry cutting, respectively. The thermal analysis indicates that the internal cooling method reduces the average surface temperature of the contact zone by 10 % when compared to dry cutting. This device has a great possibility of use by the industry because is an effective and environmentally friendly technology.